(untitled) (Biodiversitas Journal of Biological Diversity, 2006)
The research was aimed at revealing the chlorophyll content, leaf area (the plant characters), and the corm production of taro as catch crop under the young rubber stand. This research was conducted by means of Nested Design with nine replication. The intercropping planting used independent variables i.e. N0 (open condition), N1 (under the two-year-old young rubber), and N2 (under the three-year-old young rubber). The dependent variables were the chlorophyll content, leaf area, and production of the taro corm. The parameters investigated were the leaves area, the chlorophyll a and b content, the weight of fresh corm, the weight of dry corm, and the corm production per plots. The research result showed that the leaves area, and the chlorophyll a and b content significantly increased, while the weight of fresh corm, and the weight of dry corm significantly decreased (P<0.05). The fresh corm production per plots under the young rubber two- and threeyear- old were significantly decreased compared the control (P<0.05). The intercropping planting or catch crop showed that the taro corm production per plot decreased both of under two- and three-year-old young rubber shades, although the reduction of each clone was significant or not significant, so that tolerant clones could be conserved Â© 2006 Jurusan Biologi FMIPA UNS Surakarta Key words: Colocasia esculenta (L.)Schott, catch crop, plant characters, corm production